2006
DOI: 10.3166/rmpd.7.201-222
|View full text |Cite
|
Sign up to set email alerts
|

Shear Fatigue Behaviour of Tack Coats in Pavements

Abstract: International audienceFor many years, pavement engineers use mechanistic design methods that are based on algorithms to compute stresses, strains and displacements in a flexible pavement structure, or in a multi-layered structure in general. Most of these methods assume, to ease the modelling of the structure and the computation process, that the layers are fully bonded or completely unbounded to each other. Moreover, determining the effectiveness of the bonding between two layers is difficult since there is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…The experimental program was intended to perform both fatigue and oligocyclic tests, so as to span a number of loading cycles between 10 and several millions. Diakhatè et al [10] calculated stresses at the interlayer depth using the FEM code CAST3M and observed that the interface is subjected to a repetitive symmetrical alternate shearing load. The maximum shear stress value is located at the edge of the wheel.…”
Section: Dynamic Shear Testingmentioning
confidence: 99%
“…The experimental program was intended to perform both fatigue and oligocyclic tests, so as to span a number of loading cycles between 10 and several millions. Diakhatè et al [10] calculated stresses at the interlayer depth using the FEM code CAST3M and observed that the interface is subjected to a repetitive symmetrical alternate shearing load. The maximum shear stress value is located at the edge of the wheel.…”
Section: Dynamic Shear Testingmentioning
confidence: 99%
“…Previous studies have determined that appropriate characterization of interlayer bonding conditions is important to accurately predict the critical responses in the pavement structure and thereby the pavement service life [4][5][6][7][8][9][10]. However, most of pavement models introduced beforehand considered two extreme interlayer conditions including full-bond condition (i.e.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…stress-strain distribution) of layered flexible pavement system and thereby the pavement life based on the analytical and experimental results [4][5][6][7][8][9][10]. However, the current lack of thorough mechanistic characterization of the interlayer bonding condition that is able to capture the changes in critical responses for real pavement is probably the greatest deficiency in our ability to appropriately evaluate the effect of interlayer bonding condition for asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple dynamic shear test for glued three layered specimens, known as the Modified Compact Shearing (MCS) test (Millien et al, 1996, Diakhate et al, 2006 (West et al, 2005, Sholar et al, 2004, Leng et al, 2008. As depicted in Table 2.1, the devices differed in the fixing mechanism of the specimen as well as in the specimen diameter and the deformation rate of the testing of 150 mm and a width of 4.8 mm between them to hold the specimen (Sholar et al, 2004).…”
mentioning
confidence: 99%